2014
DOI: 10.3727/096368912x663541
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Cyclic Stretched Fibroblasts Accelerates the Wound-Healing Process in Streptozotocin-Induced Diabetic Mice

Abstract: Mechanical stimulation is a known modulator of survival and proliferation for many cells, including endothelial cells, smooth muscle cells, and bone marrow-derived mesenchymal stem cells. In this study, we found that mechanical strain prevents apoptosis and increases the adhesive ability of dermal fibroblasts in vitro and thus confers the survival advantage in vivo after transplantation of fibroblasts into the full-thickness wound of diabetic mice. Cyclic stretch at a frequency of 0.5 Hz and maximum elongation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…A previous study reported that MEBO enhanced α-smooth muscle actin in fibroblasts, indicating that MEBO activates fibroblasts (43). It is hypothesized that leukocytes, including fibroblasts and endothelial cells are the primary origin of VEGF and bFGF (41). Furthermore, bFGF upregulates the expression of VEGF (9,41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that MEBO enhanced α-smooth muscle actin in fibroblasts, indicating that MEBO activates fibroblasts (43). It is hypothesized that leukocytes, including fibroblasts and endothelial cells are the primary origin of VEGF and bFGF (41). Furthermore, bFGF upregulates the expression of VEGF (9,41).…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that leukocytes, including fibroblasts and endothelial cells are the primary origin of VEGF and bFGF (41). Furthermore, bFGF upregulates the expression of VEGF (9,41). Decreased levels of VEGF and/or bFGF, or inhibition of their activity leads to the limited migration of fibroblasts and the delay of wound healing (20,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblasts are proved to be able to improve the wound healing in diabetic animals[16,17]. We hypothesized that PHD2 silenced fibroblasts implantation in diabetic wound would improve wound healing and the progress would be associated with improved neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, our results add a preliminary contribution to the literature on the effects of tissue stretch on the stiffness of vaginal tissue. Other studies have shown mechanical stretch to be an important factor in extracellular protein synthesis and expression [32], upregulation of collagen [33], growth factor production(10), and changes in tissue compliance [34]. By quantifying tissue stretching with OCE, healing paradigms can be elucidated, which may define appropriate parameters for vaginal tissue mechanotherapy.…”
Section: Discussionmentioning
confidence: 99%